Management of inflammatory bowel disease patients in the COVID-19 pandemic era: a Brazilian tertiary referral center guidance - Queiroz, Natália Sousa Freitas; Barros, Luísa Leite; Azevedo, Matheus Freitas Cardoso de; Oba, Jane; Sobrado, Carlos Walter; Carlos, Alexandre de Sousa; Milani, Luciane Reis; Sipahi, Aytan Miranda; Damião, Aderson Omar Mourão Cintra (Clinics, 2020)
The world is fighting the COVID-19 outbreak and health workers, including inflammatory bowel diseases specialists, have been challenged to address the specific clinical issues of their patients. We hereby summarize the current literature in the management of inflammatory bowel disease (IBD) patients during the COVID-19 pandemic era that support the rearrangement of our IBD unit and the clinical advice provided to our patients.